2017
DOI: 10.1101/203604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stretching the skin of the fingertip creates a perceptual and motor illusion of touching a harder spring

Abstract: We investigated how artificial tactile feedback in the form of a skin-stretch affects perception of stiffness and grip force adjustment. During interactions with objects, information from kinesthetic and tactile sensors is used to estimate the forces acting on the limbs. These enable the perception of the mechanical properties of objects to form, and the creation of internal models to predict the consequences of interactions with these objects, such as feedforward grip-force adjustments to prevent slippage. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 80 publications
2
9
0
Order By: Relevance
“…However, we observed a smaller increase in the lag. One possible explanation is that the dominant peaks in the grip force were of a reactive nature and not of a predictive nature [16]. In such case, the calculation of the lag would show smaller value than 50 ms.…”
Section: Discussionmentioning
confidence: 97%
“…However, we observed a smaller increase in the lag. One possible explanation is that the dominant peaks in the grip force were of a reactive nature and not of a predictive nature [16]. In such case, the calculation of the lag would show smaller value than 50 ms.…”
Section: Discussionmentioning
confidence: 97%
“…Another proposed measure is Extended Rate Hardness, a measure of the perceived hardness of a surface based on rate of force change and penetration velocity (Han and Choi, 2010). Skin deformation accompanying the probing also likely plays a role in perception of stiffness (Quek et al, 2014, Quek et al, 2015, Farajian et al, 2017). Here, we do not attempt to spill more light on this matter, but it is possible that the estimated stiffness is used in the process of the switching.…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to understand the integration between tactile and kinesthetic information during adaptation to a force perturbation, we built a 1 DOF skin-stretch device similar to the one that was used in [4], with several modifications to fit the needs of the current study. We modified the configuration of the device such that the skin-stretch will be applied in the horizontal plane and perpendicularly to the desired movement direction ( Fig.…”
Section: Skin-stretch Devicementioning
confidence: 99%
“…Manipulation forces are the forces and torques that we exert against the held object to translate and rotate it. In contrast, grip forces stabilize the grasped object to prevent its slippage without resulting in any other motion [2][3][4]. Previously, studies showed that sensory information can be used differently to form internal representation for manipulation and grip force control [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation